2009
DOI: 10.1007/s10803-009-0803-7
|View full text |Cite
|
Sign up to set email alerts
|

Looking But Not Seeing: Atypical Visual Scanning and Recognition of Faces in 2 and 4-Year-Old Children with Autism Spectrum Disorder

Abstract: This study used eye-tracking to examine visual scanning and recognition of faces by 2- and 4-year-old children with autism spectrum disorder (ASD) (N = 44) and typically developing (TD) controls (N = 30). TD toddlers at both age levels scanned and recognized faces similarly. Toddlers with ASD looked increasingly away from faces with age, atypically attended to key features of faces, and were impaired in face recognition. Deficits in recognition were associated with imbalanced attention between key facial featu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

21
204
3
5

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 222 publications
(243 citation statements)
references
References 48 publications
21
204
3
5
Order By: Relevance
“…These claims are based on the large number of studies documenting reduced attention to faces (Hutt and Ounsted 1966;Trepagnier et al 2002;Riby and Hancock 2008;Sasson et al 2007;Bal et al 2010;Baranek 1999;Chawarska and Shic 2009;Osterling and Dawson 1994;Osterling et al 2002;Hernandez et al 2009) and/or atypical eye fixation in autism (as initially detailed in Kanner's first descriptions of autism, Kanner 1943Kanner , 1944; see also Joseph and Tanaka 2003;Riby and Hancock 2008;Boraston et al 2008;Sterling et al 2008;Jones et al 2008; for a review see Senju and Johnson 2009a). Klin et al (2002) assessed fixation patterns while participants observed emotional movie clips containing social interaction.…”
mentioning
confidence: 99%
“…These claims are based on the large number of studies documenting reduced attention to faces (Hutt and Ounsted 1966;Trepagnier et al 2002;Riby and Hancock 2008;Sasson et al 2007;Bal et al 2010;Baranek 1999;Chawarska and Shic 2009;Osterling and Dawson 1994;Osterling et al 2002;Hernandez et al 2009) and/or atypical eye fixation in autism (as initially detailed in Kanner's first descriptions of autism, Kanner 1943Kanner , 1944; see also Joseph and Tanaka 2003;Riby and Hancock 2008;Boraston et al 2008;Sterling et al 2008;Jones et al 2008; for a review see Senju and Johnson 2009a). Klin et al (2002) assessed fixation patterns while participants observed emotional movie clips containing social interaction.…”
mentioning
confidence: 99%
“…Eye-tracking studies using monitor-based technologies suggest that individuals with autism, both adults [20] as well as toddlers and preschoolage children [3], [16], show more fixations to the mouth and fewer fixations to the eyes when viewing scenes of dynamic social interactions as compared to typically developing and developmentally delayed individuals. Importantly, atypical patterns of social gaze may already be evident by 12 to 24 months of age in children who go on to receive a diagnosis of autism (e.g.…”
Section: Eye-tracking For Identifying Developmental Disordersmentioning
confidence: 99%
“…The other disorder well known to be associated with severe problems in social interaction is Autism Spectrum Disorder (ASD) and there is already a body of research investigating visual processing of faces ASD. Some eyetracking studies in ASD have shown reduced fixations on socially salient aspects of visual scenes (Noris et al, 2012;Pierce et al, 2011;Riby and Hancock, 2009 ;Rice et al, 2012) and there are reports that individuals with ASD look less at facial features (eyes, nose, 5 mouth) than typically developing peers (Chawarska and Shic, 2009;Pelphrey et al, 2002).…”
Section: How Does Trust Develop In Childhood?mentioning
confidence: 99%
“…For each participant we computed a first within-subject Pearson's correlation 11 between the profile of responses for the attractiveness and the trustworthiness tasks. Since correlation coefficients are not additive, they must be z-normalized (Chung et al, 2005) before performing statistical analyses. We thus normalized the obtained correlation coefficients by using Fisher's transform Z = 0.5 and then preformed a two-tailed t-test between groups.…”
Section: Data Analysesmentioning
confidence: 99%
See 1 more Smart Citation